Desenvolvimento de compósito de poliuretano reforçado com nanofibrilas de celulose isoladas de candeia (Eremanthus erythropappus) - Feresin, Fábio (2016)
Candeia (Eremanthus erythropappus) is an important raw material due to the essential oil that can be extracted from the whole tree. The essential oil contains (-)--bisabolol that has an active principle with pharmacological properties with wide range of use in pharmaceutical and cosmetic industries. The extraction process of essential oil produces a large quantity of wood residue that only a small portion as reused. New Developments to provide feasible alternative applications for the remaining portion of wood residue make exploration process of candeia more rentable and sustainable. Cellulose was isolated from that wood residue of candeia by wet chemistry. Further processing with an ultrafine high shear grinder the bleached cellulose pulps, with and without 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) treatment, were led to the disruption of cell walls into nanofibrils. In the present study cellulose nanofibrils (NFC) isolated from wood residue of candeia were applied as additive for a waterborne polyurethane-based wood coating in order to improve the mechanical resistance. Coating suspensions containing up to 12 wt% were prepared by mechanical mixing. The addition of cellulose nanofibers to waterborne polyurethane demonstrated the enhancement of mechanical properties. The better mechanical performances were achieved for composites with a nanofibrils amount of 8 wt% and 12 wt%. Overall the mechanical properties were increased over 40%. Additionally, the nanofibrils have acted as a rheological modifier at the waterborne coating. Cinematic viscosity increased as increased the amount of NFC. As noticed on mechanical properties behavior the effect of nanofibrils content on the viscosity is more efficient with values of 8 wt% and 12 wt%.